Nutritional management of cardiac transplanted patients. - Carlos Rafael Moret Hernandez; Johanna Diaz Landeira; Francisco José Pérez Santos; Sinay García Nidetz; Alipio Livan Gil Sosa; Abdel Felipe Pérez Navarro (ECIMED, 2012)
Transplant patients suffer from significant nutritional problems that are secondary to heart failure and its metabolic disorders made worse by the importantsurgical aggression that they need and by the effect of immune suppressing medications. All these factors justify the establishment of nutritional support inorder to reduce complications, avoid mortality, reduce costs, guarantee high quality and improve on outcome. With the objective to review the nutritionalmanagement of cardiac transplant patients during the preoperative stage, the postoperative stage in the intensive care unit and the late postoperativeperiod. We reviewed the most important healthcare databases such as Pubmed, Cochrane and Ebsco with the purpose of finding articles about nutritionand heart transplant. We used the Booleans variables. The most common words used for searching were nutrition, cardiac transplant and cardiac starvation.We found 209 articles and selected the ones which responded to the aim of the review. A review article, whose main aspects included the pathophysiologyof nutritional disorders in transplant patients, methods for nutritional assessment, preoperative and early and late postoperative treatment, wasmade. Malnutrition in patients waiting for a heart transplant has been associated with a higher rate of complications and a decreased survival rate aftertransplantation. It is essential to identify and correct nutritional deficiencies and provide an adequate nutritional support during all phases of transplantation.The main purpose of nutritional support in the immediate post transplant phase is to correct nutritional deficiencies. Prevention is the main objective ofchronic nutritional therapy after transplantation. Several metabolic complications such as diabetes mellitus, hypercholesterolemia, obesity, and hypertensionare common in patients after transplant. There isn´t enough information about the management of nutritional aspects of cardiac transplant patients. Inour country the situation is worse. Nowadays, it is extremely necessary to formulate studies about the impact of nutritional phase in the outcome of transplantpatients and in patients who undergo cardiovascular surgery in general.